Non-aromatic clusteroluminogenic polymers: structural design and applications in bioactive agent delivery. (March 2022) - Lai, Wing-Fu
Abstract: Clusteroluminescence is a phenomenon caused by the aggregation of non-conjugated electron-rich units, leading to an increase in the emission efficiency when the material is in aggregated or solid states. Because many of the non-aromatic polymers with clusterization-triggered emission features have good biocompatibility and biodegradability, along with their good processability for formulation and sustained release of a diverse range of bioactive agents, they have emerged as a new class of materials for the development of optically active carriers over the last several decades. Despite this, serious discussions on the emerging yet encouraging potential of clusteroluminogenic polymers in bioactive agent delivery have been scant in the literature till now. The objective of this article is to fill this gap by reviewing the current status of the development and use of clusteroluminogenic polymers in carrier design. It is hoped that this article can not only offer insights into the effective use of non-aromatic clusteroluminogenic polymers in carrier development but can also serve as a trigger for innovation to enhance the functionality and versatility in bioactive agent delivery research. Graphical abstract: Image 1 Highlights: Clusteroluminescence comes from the aggregation of non-conjugated electron-rich units. Non-aromatic clusteroluminogenic polymers (NCPs) can serve directly as carriers. NCP-based carriers enable the delivery process to be tracked in real time. Properties of NCPs determine the delivery performance of the generated carrier. Studies deciphering the mechanism of clusteroluminescence are needed in future research.